The Preference for Strangulation in a Sexually Motivated Serial Killer - Pettigrew, Mark (International journal of offender therapy and comparative criminology, 2019)
The existing literature on the killing method of choice for sexually motivated serial killers suggests strangulation as the preferable means of homicide, when the victim is female. When homicide victims are male, however, existing research suggests that firearms and blades are preferable methods of causing death. A case is presented here of a sexually motivated male serial killer who exclusively targeted males and who chose strangulation as his means of killing. Analysis suggests that not only is the psychological constitution of the killer an important factor in understanding how they kill victims but, also, the nature of the sexual act is an important determinant in the method of killing in male on male sexually motivated killing.